### Corrige Examen Rattrapage Analyse 2 ENS CASA 2020

Exercice : 1

soit $$\int_{0}^{4}f(x)dx=10$$ On pose $$u=2x \Rightarrow \;\;du=2dx$$ $$x=0\Rightarrow\;\;u=0\;\;et x=2\Rightarrow u=4$$ $$\Rightarrow\;2\int_{0}^{4}f(u)du=10\Rightarrow\int_{0}^{2}f(2x)dx=5$$ Soit $$\int_{0}^{9}g(x)dx=4$$ On pose $$u=x^2 \Rightarrow \;\;du=2xdx$$ $$x=0\Rightarrow\;\;u=0\;\;et x=3\Rightarrow u=9$$ $$\Rightarrow\;2\int_{0}^{9}g(u)du=4\Rightarrow\int_{0}^{3}xg(x^2)dx=2$$ Soit I_{1}=\int_{0}^{\sqrt{3}}x\sqrt{1+x^2}dx
on pose $$u=x^2+1 \Rightarrow \;\;du=2xdx$$ $$x=0\Rightarrow\;\;u=1\;\;et x=\sqrt{3}\Rightarrow u=4$$ $$I_{1}=\int_{1}^{4}\frac{\sqrt{u}}{2}du$$ $${\Rightarrow {\huge I_{1}=\frac{[\sqrt{u^3}]_{1}^{4}}{3}}}=\frac{7}{3}$$ Soit I_{2}=\int_{0}^{1}(1-2x)^9dx $$I_{2}=-2\int_{0}^{1}-2(1-2x)^9dx$$ $$I_{2}=2\int_{1}^{0}-2(1-2x)^9dx$$ $$I_{2}=[\frac{(1-2x)^{10}}{5}]_{1}^{0}=0$$ Soit I_{3}=\int_{0}^{\pi}\sin(t)\sqrt{1+\cos(t)}dt
on pose $$u=1+\cos (t)\Rightarrow\;du=-\sin(t)dt$$ $$t=0\Rightarrow\;u=2 \;et\;t=\pi\Rightarrow\;u=0$$ $$I_{3}=\int_{0}^{2}\sqrt{u}du=2[\frac{\sqrt{u^3}}{3}]_{0}^{2}=\frac{4\sqrt{2}}{3}$$ Soit I_{4}=\int_{0}^{4}(4-t)\sqrt{t}dt $$=\int_{0}^{4}4\sqrt{t}dt-\int_{0}^{4}t\sqrt{t}d$$ $$=8[\frac{\sqrt{t^3}}{3}]_{0}^{4}-2[\frac{\sqrt{t^5}}{5}]_{0}^{4}$$ $$I_{4}=\frac{64}{3}-\frac{64}{3}=0$$ Exercice: 2

Soit $$f^{"}(t)=t^2+\frac{1}{t^2}$$ Donc $$f^{'}(t)=\frac{t^3}{3}-\frac{1}{t}+a$$ $$f(t)=\frac{t^4}{12}-\ln (t)+at+b$$ $$f(2)=3=\frac{16}{12}-\ln (2)+2a+b$$ $$f^{'}(1)=\frac{1}{3}-\frac{1}{1}+a=2$$ $$\Rightarrow a=\frac{5}{3}\, et \,b=5+\ln (2)$$ $$f(t)=\frac{t^4}{12}-\ln (t)+\frac{5t}{3}+5+\ln (2)$$ Soit $$f^{"}(x)=24x^2+6x$$ Donc $$f^{'}(x)=8x^3+3x^2+a$$ $$f(x)=2x^4+x^3+ax+b$$ $$f(0)=3=b$$ $$f(1)=10=2+1+a+b$$ $$\Rightarrow a=4\, et \,b=3$$ $$\Rightarrow f(x)=2x^4+x^3+4x+3$$ Soit f^{"}(t)=\cos (t)+\sin (t)
Donc f^{'}(t)=\cos (t)-\sin (t)+a`
$$f(t)=-\cos (t)-\sin (t)+at+b$$ $$f(0)=3=-1+b$$ $$f^{'}(0)=4=1+a$$ $$\Rightarrow a=3\, et \,b=4$$ $$\Rightarrow f(t)=-\cos (t)-\sin (t)+3t+4$$
Exercice 3
Soit $$y^{"}(x)+3 y^{'}(x)+2 y(x)=0$$ $$r^{2}+3 r+2 =0$$ $$\Delta=3^2-4\times2=1$$ $$\longleftrightarrow r_{1}=\dfrac{-3-\sqrt{\Delta}}{2}=\dfrac{-3-1}{2}=-2$$ $$r_{2}=\dfrac{-3+\sqrt{\Delta}}{2}=\dfrac{-3+1}{2}=-1$$ Donc $$y(x)=A\exp (-x)+B\exp (-2x)$$ $$y(0)=1=A+B$$ $$y^{'}(0)=0=-A-2B$$ $$\Rightarrow A=2\, et \,B=-1$$ $$\Rightarrow y(x)=2\exp (-x)-\exp (-2x)$$